A contribuição da pesquisa-ação na construção do conhecimento científico na Engenharia de Produção brasileira - Gibertoni, Daniela (2012)
The main subject of this thesis is the action research and has as general objective describe the construction of knowledge in the action research field from the uses that Brazilian production engineers make of it, aiming to recognize its contributions, potential and limits. To achieve this goal, it was needed a literature review on national and international literature to later contrast with the national academic researches that use action research and show its uses to overcome the main obstacles faced. It´s shown the main features and currents of the action research, which emerged over the years, due to historical and cultural factors, and also to the practical needs arising from the research. Thus, there are characteristics that unify the action research, as well as differences. Identified these similarities and differences, a documentary research was carried out in academic papers published in National Meeting of Production Engineering (ENEGEP) from 1996 to 2010. 191 articles were analyzed, searching for the answer to the question: which use is made of the action research in Production Engineering in Brazil that allows to identifying the types of knowledge generated by it? The content analysis was the strategy used for the treatment of data, using NVivo software of the company QSR International. Through this software it was possible to do an analysis with a qualitative approach. With the analysis were identified some researchers who make use of action research very often in their researches. With these data, semi-structured interviews were made with seven researchers. It was noticed that in some sub-areas of Production Engineering there is a higher use, such as in the sub-area of information systems, product development and knowledge management. Even in other sub-areas we notice that the use of action research takes place mainly because it is a real study, combining theory and practice. This means, that the greatest knowledge that the researcher seeks to obtain when using the action research is the practical application in a given sector, promoting during the intervention the changing process and consequently the learning.